PENINGKATAN KREATIVITAS SISWA MELALUI PEMANFAATAN ALAM SEKITAR DALAM PEMBELAJARAN IPA KELAS IV SD - Muharianto, Wendi; Kaswari, Kaswari; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is how to increase the creativity of students through the utilization of the natural surroundings in the science of science class IV State Elementary School 30 Pontianak North. The research method used is descriptive with the form of action research class. Research subjects are teachers as researchers and students of class IV which amounted to 37 people. The procedure consists of planning, implementation, observation and reflection. The data collected is the data ability of teachers to design and implement learning, as well as student creativity data. Technique of data collection is direct observation. The data collection tool is the teacher and student observation sheet. Data analysis is the ability of teachers to design and implement learning, and the value of creativity of students using the calculation of the average. The results obtained are the ability of teachers to plan overall learning obtained an average score of 3.20. The ability of teachers to implement the overall learning obtained average score 3.25. Student creativity as a whole has an average score of 3.00. Thus the creativity of students through the utilization of natural surroundings in science learning has increased. Keywords: Creativity, Natural Utilization, Science Lesson.